2013
DOI: 10.1099/ijs.0.052126-0
|View full text |Cite
|
Sign up to set email alerts
|

Coprobacter fastidiosus gen. nov., sp. nov., a novel member of the family Porphyromonadaceae isolated from infant faeces

Abstract: A novel obligately anaerobic, non-spore-forming, rod-shaped, non-motile Gram-reaction-negative bacterium was isolated from infant faeces. The strain, designated NSB1T, was able to grow on rich media at 30–37 °C, in the presence of up to 2 % (w/v) Oxgall and 2 % (w/v) NaCl. Cells of strain NSB1T produced catalase, but not urease and indole. Aesculin was not hydrolysed. The strain was able to utilize d-glucose, lactose, maltose, mannose and raffinose as electron donors. When grown on d-glucose, the main metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 38 publications
(38 reference statements)
4
27
0
Order By: Relevance
“…In female mice, DHA specifically decreased the abundance of pro‐inflammatory Enterorhabdus [ 54 ] and promoted the growth of butyrate‐producing Intestinimonas [ 55 ] and Bacteroides acidifaciens [ 56 ] which were shown to prevent obesity and improve insulin sensitivity. EPA specifically favored SCFA‐producing Coprobacter , [ 57 ] Alloprevotella, [ 58 ] and Anaerotruncus . [ 59 ] These shifts in gut microbiome indicated that EPA and DHA differentially reversed gut dysbiosis which may further improve the intestinal barrier and affect the production of microbial metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…In female mice, DHA specifically decreased the abundance of pro‐inflammatory Enterorhabdus [ 54 ] and promoted the growth of butyrate‐producing Intestinimonas [ 55 ] and Bacteroides acidifaciens [ 56 ] which were shown to prevent obesity and improve insulin sensitivity. EPA specifically favored SCFA‐producing Coprobacter , [ 57 ] Alloprevotella, [ 58 ] and Anaerotruncus . [ 59 ] These shifts in gut microbiome indicated that EPA and DHA differentially reversed gut dysbiosis which may further improve the intestinal barrier and affect the production of microbial metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the genus Coprobacter , family Rikenellaceae , is currently restricted to a single species, Coprobacter fastidiosus , isolated from faeces of a healthy infant (Shkoporov et al , 2013). The closely related genus Barnesiella comprises only two known species, Barnesiella intestinihominis (Morotomi et al , 2008), commonly found in the human faecal microbiota at concentrations exceeding 10 9 c.f.u.…”
mentioning
confidence: 99%
“…Currently, it comprises a single species, Coprobacter fastidiosus , isolated from the feces of a healthy infant (6). These Gram-negative obligate anaerobic bacteria differ from members of a closely related genus, Barnesiella , by their ability to produce propionic acid, their lower G+C content, and the composition of their major fatty acids.…”
Section: Genome Announcementmentioning
confidence: 99%
“…These Gram-negative obligate anaerobic bacteria differ from members of a closely related genus, Barnesiella , by their ability to produce propionic acid, their lower G+C content, and the composition of their major fatty acids. The abundance of 16S rRNA sequences of C. fastidiosus in metagenomic studies suggests this species is highly prevalent in human intestinal microbiota (6). …”
Section: Genome Announcementmentioning
confidence: 99%
See 1 more Smart Citation